EVALUATION OF VALPROIC ACID DOSE USED FOR PAEDIATRIC WITH EPILEPSY - Herningtyas Nautika Lingga; Lukman Hakim; I Dewa Putu Pramantara (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Epilepsy is a chronic disease in neurology and the second most common disorder after stroke. Valproic acid is categorised to the medicine with a narrow therapeutic index which requires monitoring of plasma drug levels and dose adjustments to prevent toxic effects. This study aimed to determine the estimated value of valproic acid concentration in serum and clinical outcomes in paediatric patients with epilepsy observed from seizure-free duration at Sleman Regional General Hopital, Yogyakarta. This study was a retrospective study with descriptive observational design. Subjects were paediatric patients with epilepsy who received valproic acid treatment over the period of January 2010-December 2012, 1 to 18 years old, boys or girls who were routinely controlled for at least 6 consecutive months. Clinical outcomes were observed through the duration of the seizure-free which were devided into 2 categories i.e. <6 months (unfavorable outcome), and ≥ 6 months (a good outcome). The proportion of 99 patients who met the inclusion criteria were 27.28% less than or equal to 5 years old, whereas 5-12 years and 12-18 years age groups had the same percentage which was 36.36%. From the calculation, average estimated value of valproic acid concentrations in serum for girls group were as much as 86.32±49.25 mg/L and 33.26±22.06 mg/L, while in boys group were as much as 94.91±44.72 mg/L and 38.57±20.72 mg/L. Based on the duration of seizure free, clinical outcome showed that the percentage of patients in monotherapy group had good and poor outcomes with 52.33% and 46.67% respectively, while 61.54% and 38.46% of patients in polytherapy group had good and poor outcome respectively.Keywords: Epilepsy, Valproic Acid, Clinical Outcome, Paediatric